Value of Intraoperative Neuromonitoring in Spinal Tuberculosis Surgery: Case Report of Neurological Compromise with Normal Imaging - Kumar, Yogesh; Kumar, Avinash; Tasneem, Zakiyyah; Sivasubramanian, Nirangjhana (Asian Journal of Neurosurgery, 2025)
Spinal tuberculosis (TB), also known as Pott's spine, remains a significant cause of spinal deformity and neurological compromise, particularly in endemic regions. Surgical correction of chronic deformities is associated with significant risks, including spinal cord injury. Intraoperative neurophysiological monitoring (IONM) has become an essential tool to minimize neurological complications. We report a case of an adolescent boy with longstanding thoracolumbar kyphosis due to spinal TB, where IONM identified true positive motor pathway compromise during deformity correction, despite intraoperative C-arm imaging confirming correct pedicle screw placement. Surgery was halted, and staged completion was planned. Postoperative neurological deficits confirmed the predictive validity of IONM. This case highlights the indispensable role of IONM in surgical decision-making, particularly in complex TB-related deformities where imaging alone may be insufficient to prevent neurological injury.
Keywords: Pott's spine; spinal tuberculosis; intraoperative neuromonitoring; kyphotic deformity; spinal cord injury